Close Intubation of Lacrimal Drainage System in Children. - HUSSAIN, M; AKHTAR, S; CHOUDHRY, M A; DIN , N (Annals of King Edward Medical University, 2020)
A retrospective study was conducted at Eye Deptt. Lahore General Hospital Lahore for epiphora in children. We performed closed intubation in 19 children where syringing and probing had failed twice at least. All the patients were done under General Anesthesia. In three patients we had collaboration of ENR surgeon. We had success rate of 84.2%. Our procedure failed in three patients, we had to do dacryocystorhinostomy (DCR) in one 8 years old patient. The rest of the two patient had no relief of epiphora and discharge.